Peran Strategis Pemerintah Kabupaten Gunungkidul Dalam Pengembangan Sektor Pariwisata Pantai Midodaren - Lestari, Puji; Yuliani, Isnaeni (PANDITA: Interdisciplinary Journal of Public Affairs, 2025)
Midodaren Beach, which is located in Gunungkidul Regency, is famous for its amazing natural beauty so that it has opportunities in the development of tourist destinations in Gunungkidul Regency. This research use qualitative descriptive and data obtained through observation, interviews, and literature study. The analysis is used to describe and solve problems systematically using the SWOT analysis method, namely to see the extent of the implementation of the Midodaren Beach tourism object development strategy. The purpose of this study is to find out the obstacles and strategies of the Gunungkidul Regency government in the development of Midodaren Beach tourism objects based on strengths, weaknesses, opportunities, and threats. Midodaren Beach must be promoted optimally, so that it will attract tourists to visit Midodaren Beach. The obstacles faced in the development of Midodaren Beach are limitations in funding. The Gunungkidul Regency Government needs to collaborate with related parties in terms of funding, so that Midodaren Beach can become a tourist attraction in Gunungkidul Regency. The development strategy of Midodaren Beach tourist attractions is carried out by collaborating with the Gunungkidul Regency government with the private sector in improving facilities and infrastructure on Midodaren Beach.